Response of Cowpea (Vigna unguiculata) to Inorganic and Biofertilizers - N.K. Kalegore; M. A. Gavhane; S. A. Bhusari; S. V. Kasle; R. S. Dhamane (International Journal of Economic Plants, 2018)
A field experiment was conducted to study the Effect of inorganic and biofertilizers on growth and yield of cowpeaat Agronomy section, College of Agriculture, VNMKV, Latur, India. The experimental field was levelled and well drained. The soil was clayey in texture, moderate in nitrogen (216 kg ha-1), medium in phosphorous (16.54 kg ha-1), high in potash (465 kg ha-1) and moderate alkaline in nature (8.02 pH). The experiment was laid out in a factorial randomised block design. Each experimental unit was replicated three times. The gross and net plot size of each experimental unit was 5.4×4.2 and 4.8×3.6 m2 respectively. There were nine treatment combinations of levels each of RDF and bio fertilizer viz. 75% RDF, 100% RDF, per cent RDF and Seed inoculation of PSB, Seed inoculation of rhizobium, dual seed inoculation of PSB+Rhizobium. Application of 125% RDF was recorded significantly higher growth and yield contributing characters viz. plant height (92.8 cm), no. of branches plant-1 (8.7) no. of functional leaves plant-1 (29.6), dry matter plant-1 (23.6 g) and no.of seeds plant-1 (66.1), no of pods plant-1 (8.6) pod yield plant-1 (7.98 g), seed yield kg ha-1 (1564), straw yield (3881 kg ha-1) and seed index (8.7 g) respectively over the application of 75% RDF. Dual inoculation of PSB+Rhizobium culture was found superior than alone PSB treatment in respect of growth and yield parameters